Trade openness, foreign direct investment and industrialisation in Ghana - Patrick Kwashie Akorsu; Samuel Okyere (Cogent Economics & Finance, 2023)
The industrialisation of the Ghanaian economy has seen less light despite the high levels of trade and being one of the highest receivers of foreign direct investment (FDI) in West Africa. This low performance in the industrial sector may be due to the frequent shocks the country suffers in her trade engagements and FDI inflows. Therefore, this study sought to examine the asymmetric effect of trade openness and FDI on industrialisation in Ghana. In achieving this, contemporary time series approaches, involving Autoregressive Distributed Lag (ARDL) and Non-Linear Autoregressive Distributed Lag (NARDL) approaches to cointegration, were used to analyse the time series data from 1983 to 2019. The results revealed that in both the long- and short-run, the positive shocks in trade openness have no effect on industrialisation, and the negative shocks in trade openness cause industrialisation to fall. Regarding FDI, the positive shocks in FDI exert positive effect on industrialisation in both the long- and short-run, but the negative shocks exert no effect on industrialisation in the long-run, however, a positive effect on industrialisation in the short-run. Findings from the study imply that trade openness in both the long- and short-run is detrimental to industrial progress in Ghana. Also, FDI is much needed for Ghana to industrialise her country. It is recommended that government policies should be channelled to reducing external shocks faced by traders, mostly exporters, while focusing on creating an enabling environment to attract the needed FDI to the industrial sector, and increasing infrastructural base of the country.
Keywords: 330; asymmetric relationships; industrialisation; non-linear autoregressive distributed lag; stability